Evaluation of Tissue Doppler Echocardiographic Imaging findings in children with pulmonary hypertension - Alper Akın; Dursun Alehan; Hayrettin Hakan Aykan; Süheyla Özkutlu; Sema Özer; Tevfik Karagöz (The Turkish Journal of Pediatrics)
Tissue Doppler Imaging has become an important prognostic marker that can be used in follow-up and determination of the prognosis in pulmonary hypertension patients. We compared the Tissue Doppler imaging parameters of 34 patients with pulmonary hypertension and 43 healthy controls. In addition, Brain-Natriuretic Peptide levels, pulmonary artery systolic pressures measured with echocardiography, 6-minute walking tests and New York Heart Association functional classification were compared. Among patients with Eisenmenger syndrome and idiopathic pulmonary hypertension, Tissue Doppler imaging parameters were mostly similar. In patients with New York Heart Association functional class 3, mitral septal annulus E/Ea (p=0.050) and mitral lateral annulus myocardial performance index (p=0.009) were higher than class 2 patients. In patients with higher Brain Natriuretic Peptide level, mitral lateral annulus and tricuspid septal annulus Ea/Aa values were lower (p=0.046 and < 0.001 respectively); tricuspid septal annulus E/Ea and interventricular septum myocardial performance index values were higher than in patients with normal Brain-Natriuretic Peptide level (p=0.006). In conclusion tissue Doppler imaging findings were significantly impaired in children with pulmonary hypertension compared to the control group. Findings were similar in patients with idiopathic pulmonary hypertension and Eisenmenger syndrome. Mitral lateral annulus myocardial performance index value may have a prognostic importance due its significant association with poor functional class. Due to the significant associations between mitral lateral annulus, tricuspid septal annulus Ea/Aa, tricuspid septal annulus Ea and E/Aa, interventricular septum-myocardial performance index values and brain natriuretic peptide levels, these parameters may be used in evaluating response to therapy.